Effect of Psychotherapy on Reduction of Fear of Childbirth and Pregnancy Stress: A Randomized Controlled Trial - Abdollahi, Somayeh; Faramarzi, Mahbobeh; Delavar, Mouloud Agajani; Bakouei, Fatemeh; Chehrazi, Mohammad; Gholinia, Hemmat (Frontiers in Psychology, 2020)
Introduction The fear of childbirth (FOC) has an adverse effect on the physical and mental health of pregnant women and increases adverse maternal and fetal outcomes. Previous research reported the effect of psychological interventions such as cognitive behavioral therapy, relaxation therapies, and short-term psycho-educational intervention on FOC. We examined whether adding motivational interviewing (MI) psychotherapy to prenatal usual care (PUC) is superior to PUC alone to reduce the scores of FOC, pregnancy stress, and self-efficacy. Materials and Methods An RCT with two-arm parallel groups and 1:1 allocation ratio assigned 70 pregnant women (aged 18–50) attending public health centers in an education hospital in Iran to receive five sessions of group MI psychotherapy plus PUC (N = 35) or to receive PUC alone (N = 35). The primary outcomes were the FOC scores (Wijma Delivery Expectancy/Experience Questionnaire, W-DEQ), pregnancy-specific stress (Prenatal Distress Questionnaire, NuPDQ), anxiety (Spielberger state anxiety), and Childbirth Self-Efficacy Index (CBSI) at 5 weeks post-randomization. Additional measures included subscales of the W-DEQ and the NuPDQ, patients’ compliance, and satisfaction with psychotherapy intervention at 5 weeks post-randomization as secondary outcomes. Main Results The post-trial results indicated that the outcome scores diminished more considerably in psychotherapy than in PUC for total FOC scale with a large effect size (B = −23.54, p = < 0.001, η2η2 = 0.27), for total pregnancy stress with a large effect size (B = −4.51, p = < 0.001, η2 = 19), and for state anxiety with a large effect size (B = −12.42, p = < 0.001, η2 = 0.22). However, the score of self-efficacy and concern about physical symptoms did not differ between the psychotherapy and PUC groups (P < 0.05). Discussion Adding 5 weeks of group psychotherapy to PUC could be considered as an adjunctive care option for reducing FOC, pregnancy stress, and general anxiety in pregnant women in the third trimester. Future research may focus on sustaining the effects and evaluating the economic impacts of adding psychotherapy to PUC.